Graded exercise therapy for patients with chronic fatigue syndrome in secondary care – a benchmarking study. Issue 20 (25th September 2022) - Smakowski, Abigail; Adamson, James; Turner, Tracey; Chalder, Trudie
Abstract: Objective: We investigated the effectiveness of graded exercise therapy (GET) delivered to patients with chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) in a routine, specialist clinic by measuring patient-reported outcome data collected prospectively over several timepoints alongside therapy. Benchmarking analyses were used to compare our results with those found in randomised controlled trials (RCTs). Methods: Data were collected from patients, with a diagnosis of CFS/ME, who had been referred to a specialist clinical service in South London. Measures included Chalder Fatigue Questionnaire, Physical Functioning Subscale of the Short-Form Health Questionnaire, and the Work and Social Adjustment Scale. Change on each measure was calculated over time using linear mixed-model analyses. Within group effect sizes were calculated and compared with previous RCTs. Results: Fatigue scores were significantly reduced by session 4 (–5.18, 95%CIs −7.90, −2.45) and at follow-up (–4.73, 95%CIs −7.60, −1.85). Work and social adjustment and physical functioning progressively improved over the course of therapy, reaching significance at discharge and maintained at follow-up (WSAS −4.97, 95%CIs −7.97, −1.97; SF-36 10.75, 95%CIs 2.19, 19.31). Conclusions: GET is an effective treatment for CFS/ME within clinical practice. However, effect sizes were smaller in routine clinical practice than RCTs suggesting that avenues for augmentation need to be considered. Implications for rehabilitation: It is important to assess whether patient reported outcomes of treatments that have been evaluated in the context of clinical trials are similar in routine clinical practice. This study shows fatigue severity, physical functioning, and work and social adjustment can significantly improve after graded exercise therapy for patients with chronic fatigue syndrome within a specialist service. Benchmarking methods showed clinical outcomes obtained smaller effect sizes than randomised controlled trials – techniques to maximise patient outcomes should be considered.